Effect of NPK fertilizers on growth, yield and yield attributes of okra (Abelmoschus esculentus (L.) Moench.) (Bangladesh Journal of Botany, 2013)
Five different doses of NPK fertilizers, viz. To (0N0P0K), T1 (1N1P1K), T2 (0N1P1K), T3 (1N0P1K) and T4 (1N1P0K) were applied and the growth, yield and yield attributes of okra were studied. The length of main stem, number of nodes and leaves were maximum at T1. The fresh weight, length, circumference, diameter per fruit and yield per plant were the highest at T1. The carotenoid content of leaves and vitamin C contents of fruits were maximum at T1. The total NPK concentration of both plants and fruits were the highest at T3. DOI: http://dx.doi.org/10.3329/bjb.v41i2.13436 Bangladesh J. Bot. 41(2): 131-134, 2012 (December)